P41 Exploring the impact of moulage on assessment of patient deterioration. (5th November 2017) - Hogg, G; Christie, P
Abstract : Background: In recent years, the use of simulation has dramatically increased within medical education. As a simulation tool, moulage aims to make scenarios as realistic as possible through the application of makeup to represent physical damage or deterioration. At Dundee Medical School, moulage is used within the clinical skills centre to create mock injuries for Year 5 Trauma Days. Aims: This action research project aims to determine the impact of moulage on how students assess physical deterioration of patients during these sessions. This will explore the usefulness and realism of the makeup, as well as student's previous exposure to moulage in other learning experiences. The project also aims to determine the key factors which influence the impact of the moulage. Methods: An action research philosophy was chosen as the methodology for this study, with the aim of completing one full cycle. A mixed methods approach was also chosen. An online questionnaire was distributed to Year 5 students, and focus groups were conducted with Year 1 simulated patients. Results: Both students and staff agreed that moulage helped bring focus to areas of trauma, improved realism of scenarios, allowed simulations to run smoothly and that the effect of moulage was decreased by unrealistic clothing. Additionally, the students felt that the moulage in burns and bruising stations were particularly effective and that the effect of moulage was decreased by unrealistic patient scenarios. The simulated patient participant group also revealed that trained individuals were found to provide better application of moulage; there was limited time for moulage application and finally, moulage helped actors to remain in their roles. Discussion and Conclusion: Moulage was found to be a useful simulation tool, due its ability to enhance the realism of scenarios, to draw focus to areas of injury and to allow the cases to run smoothly. However, there were also found to be several factors which limited the quality of the moulage, specifically the time allowed for its application, and the training and experience held by those applying the moulage. Certain aspects of the simulation were also found to be unrealistic, reducing the effect of the makeup. These areas include the acting and the clothing worn by the simulated patients. In future, it is recommended that more time is given to the moulage application, but additionally, realism of all aspects of the scenario is increased, in order to make the use of moulage worthwhile.